Kilbrandon - then, now, and in the future - Malcolm Schaffer (Scottish Journal of Residential Child Care)
The 50th anniversary of the publication of the Kilbrandon report provides an opportunity to reflect on the impact that the report has had on vulnerable children in Scotland and consider the system's future prospects. The Kilbrandon vision and values have had a profound effect on our legal system and Scottish society at large. The writer declares that, having been involved in Children's Hearings for over 40 years, the views expressed within this paper are not completely neutral. Now is an appropriate time to take stock of the extent to which Kilbrandon's vision remains alive today and to reflect on the changes that have occurred over the years in terms of politics, society, the law and organisational structures. It is also an opportunity to consider how our contemporary knowledge of vulnerable children’s needs, and rights, have influenced the development of the Children's Hearing system. This article considers the ways in which the system might adapt in future to ensure that the core values of Kilbrandon continue to influence future policy making concerning the needs of Scotland's children.